1989
DOI: 10.1159/000120473
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Arachnoid Cysts in Children

Abstract: Congenital arachnoid cysts (CAC) are benign developmental disorders. A number of theories have been proposed to explain the origin and progression to the symptomatic stage. Management strategies range from not treating the asymptomatic cysts to craniotomy, excision of cyst wall and establishment of a communication with the adjacent subarachnoid cistern or ventricle. Other lesions may resemble CAC, and can be differentiated from CAC only by a critical review of the biopsy specimen. We have reviewed our experien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…We attribute much o f our recent success in group 2 patients to more aggressive, open fenestration procedures where multiple openings in the cyst wall are best achieved, while at the same time making our cranioto mies progressively smaller. The overall 14% complication rate and the 0% mortali ty rate in our series (table 5) compare favorably to other pediatric series reported in the literature [7,15,22]. The rate o f postoperative complications declined from group 1 (16%) to group 2 (13%).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…We attribute much o f our recent success in group 2 patients to more aggressive, open fenestration procedures where multiple openings in the cyst wall are best achieved, while at the same time making our cranioto mies progressively smaller. The overall 14% complication rate and the 0% mortali ty rate in our series (table 5) compare favorably to other pediatric series reported in the literature [7,15,22]. The rate o f postoperative complications declined from group 1 (16%) to group 2 (13%).…”
Section: Discussionsupporting
confidence: 83%
“…There continues to be a lack o f consensus as to which method provides the optimal management o f these le sions for particular patients. Numerous reports have claimed good results primarily with fenestration [6][7][8][9][10][11][12][13][14], while others recommend C P shunting [15][16][17][18][19][20]. Although the European cooperative study performed by Oberbauer et al [21] reported that craniotomy with fenestration was the most common surgical approach, the debate continues regarding the best surgical treatment.…”
Section: Introductionmentioning
confidence: 99%
“…True arachnoid cysts are congenital lesions [22] that are thought to arise from abnormal splitting or duplication of the arachnoid membrane during development [23,24,25,26]. Secondary arachnoid cysts, on the other hand, may result from trauma [27, 28], infection or hemorrhage in the subarachnoid space [29].…”
Section: Discussionmentioning
confidence: 99%
“…Many institutions, such as ours, have favored initial cyst fenestration, usually into the basal cisterns. 4,7,8,11,13,14,16,21,23,25,28 Other centers have advocated the placement of CP shunts as a primary treatment for these cysts. 3,27 The clinical presentation of patients with arachnoid cysts, especially during the first few years of life, may offer considerable insight into the relationship between these lesions and underlying aberrancies in CSF flow.…”
mentioning
confidence: 99%